A hardware ımplementation of an open-source qibla direction finder with tilt compensation using 9-dof ımu and gps - Tawil, Yahya (Institute of Electrical and Electronics Engineers Inc., 2023)
The Qibla serves as the orientation for Muslims during prayer, indicating the direction towards the Kaaba in the Sacred Mosque of Mecca. Previous works of Qibla finder devices considered the ideal condition, only, of operating on a flat surface, and additionally did not study the importance of compass calibration. The proposed Hardware implementation studied the tilt compensation and compass soft-iron and hard-iron calibration. Without the tilt compensation and compass calibration, finding the Qibla direction will prone to error. The Qibla error without tilt compensation can reach up to 100 degrees for 30 degrees pitch. The proposed design uses out-of-the-shelf 9DOF (9 Degrees of Freedom) IMU (Inertial Measurement Unit), and an optional GPS receiver to get the location. The accelerometer and gyroscope data, with a complementary filter, are used to calculate the pitch and roll angles which are used in tilt compensation. The magnetometer is used to calculate the azimuth. The Qibla direction is calculated using modern trigonometry after compensating the magnetometer readings for tilt. The proposed design is compared with reference Qibla direction in mosques and using the Qibla finder mobile application. This work achieved a robinder device with possible tilt on X-axis sust Qibla calculation with pitch and roll tilt less than 90 degrees allowing the Qibla finder to be functional with accepted error in more environments compared to the ideal case of having a flat surface. © 2023 IEEE.
Keywords: 3-axis digital compass; Calibration; Hardware implementation; Qibla finder; tilt-compensated